A FINDING OF THE EARLY PERIOD IN THE ASIA VALLEY - Ángeles Falcón, Rommel (2002)
lt is presented onefuneral contextfrom the low valley ofAsia, located at 100 kilometers in the south ofLima. The associated materials indicate the presence of obsidian points, bone sculptures and anthracite mirror, between other vestiges. This takes us to plan that the Asia valley was notstrange to ideologies traffic or the interaction of coast and highland societies during this period where ideological aspects played a fundamental role. /t is presented in the same way the architectonic characteristics and the settlement pattern ofthe valley during the Formative period, it is pointed too, the existing differences between Lima coast and the north central coast, determined in that one the absence ofmonumental public architecture.